Improving coherence scanning interferometry signal modelling and topography measurement for complex surfaces - Thomas, Matthew (2022)
This thesis presents work on advanced optical surface metrology methods that enable extending the range of surface slopes that can be reliably measured by optical surface topography measurement instruments, and on investigating the reliability of the current capability. Optical instruments can only capture a limited portion of light scattered from an object’s surface, determined by the instrument’s numerical aperture. As the surface measured becomes steeper, less scatter is captured until all specular scatter is lost, referred to as the specular reflection limit (SRL). While surface measurement of slopes beyond the SRL by modern instruments is possible via the capture and detection of non-specular scatter, the instrument response to these slopes is not well understood. In addition, as the non-specular scatter has a low signal-to-noise ratio, data dropout can occur. Topography measurement of steep and complex surfaces using optical methods can therefore be challenging and have an unknown reliability, and can have significant errors when multiple scattering is present.